Constraints on Productivity and Investment in Indonesia's Manufacturing Sector Survey-based Analysis of Business Constraints - Ing, Lili Yan (The World Bank, 2012)
Well-functioning markets, adequate infrastructure and simple and clearly defined regulations are some of the characteristics of a growth-enhancing business climate. In Indonesia, some of these elements are missing, which challenges firms' operations. This note discusses the main constraints that Indonesia's manufacturing firms face, shows that these differ depending on the nature of the firm and examines the effect of these constraints on firms' productivity and decisions to invest. It concludes that the poor business climate has substantial costs in terms of firms' productivity and growth. Some broad policy recommendations emerge, and are related to improving credit information, providing microfinance for productive start-ups, improving infrastructure particularly electricity and logistics, incentivizing training, increasing collective action on sharing knowledge, improving tax administration including shortening the time for Value Added Tax (VAT) refunds and duty drawbacks, as well as strengthening law enforcement on business contracts. Addressing these constraints is not merely a task for the Government of Indonesia, but also one for the private sector. It is the Government's responsibility to set clear business regulations, as well as improve the business environment, but it is the private sector's responsibility to take action on sharing knowledge and developing its clusters